Chronic secondary orofacial pain as the first symptom of chronic non-bacterial osteomyelitis in the mandible: a case report and literature review - Braga, Samilla Pontes; Neves , Raniel Ramon Norte; Jales , Sumatra Melo da Costa Pereira; Rocha, André Caroli; Pereira , Rosa Maria Rodrigues; Siqueira, José Tadeu Tesseroli de (Brazilian Journal of Case Reports, 2024)
Chronic non-bacterial osteomyelitis clinically manifests with pain, swelling and limitation of movement. When it affects the jaws, it can cause pain, similar to other orofacial conditions, requiring a correct differential diagnosis. The objective of this study was to report a clinical case of chronic secondary orofacial pain as the first manifestation of an inflammatory bone disease located in the mandible, in addition to discussing the diagnostic hypotheses, the pathophysiological aspects and the therapy. A 21-year-old male patient came to the service complaining of pain in the mandible, preauricular and temporal regions bilaterally with one year of evolution, associated with anterior open bite and psychological impairment. So, it was chronic orofacial pain secondary to non-bacterial osteomyelitis with a high rate of bone remodeling. Elevation of pro-inflammatory cytokines can lead to an increased power cycle of nociceptive signaling, chronic inflammation, and bone loss. Pro-inflammatory cytokines that originate in neuronal and glial cells can trigger effects such as chronic hyperexcitability, changes in the phenotypic expression of nociceptors and abnormal processing of noxious signals. The patient is still undergoing treatment and without pain. Careful assessment, ordering tests and multidisciplinary investigation are essential in the care of patients with chronic and complex orofacial pain.